2016
DOI: 10.1016/j.actbio.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the strength and bioactivity of collagen scaffolds using customizable arrays of 3D-printed polymer fibers

Abstract: Tendon is a highly aligned connective tissue which transmits force from muscle to bone. Each year, people in the US sustain more than 32 million tendon injuries. To mitigate poor functional outcomes due to scar formation, current surgical techniques rely heavily on autografts. Biomaterial platforms and tissue engineering methods offer an alternative approach to address these injuries. Scaffolds incorporating aligned structural features can promote expansion of adult tenocytes and mesenchymal stem cells capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…One set of fiber arrays was comprised of uniform fiber architecture along its length; these arrays were created using sinusoidal fiber architectures with either a 1 mm or 2 mm sinusoidal amplitude. This first group ( continuous ) displayed the same geometries reported in our previous work using ABS fibers (Mozdzen et al, 2016). Here, fiber arrays were either linear (straight fiber array: Straight ) or were sinusoidal with a set period (11.3 mm) and one of two amplitudes (1 mm sinusoidal fiber array: 1 mm Amp ; 2 mm sinusoidal fiber array: 2 mm Amp ).…”
Section: : Materials and Methodssupporting
confidence: 76%
See 3 more Smart Citations
“…One set of fiber arrays was comprised of uniform fiber architecture along its length; these arrays were created using sinusoidal fiber architectures with either a 1 mm or 2 mm sinusoidal amplitude. This first group ( continuous ) displayed the same geometries reported in our previous work using ABS fibers (Mozdzen et al, 2016). Here, fiber arrays were either linear (straight fiber array: Straight ) or were sinusoidal with a set period (11.3 mm) and one of two amplitudes (1 mm sinusoidal fiber array: 1 mm Amp ; 2 mm sinusoidal fiber array: 2 mm Amp ).…”
Section: : Materials and Methodssupporting
confidence: 76%
“…The final group of fiber arrays also displayed discontinuous geometries, but contained a gradual transition across its length (straight; ¼ amplitude, ½ amplitude, full amplitude) using both the 1 mm and 2 mm sinusoidal fiber array ( gradient: 1 mm Amp, 2 mm Amp ) (Figure 1). We have previously published detailed methods regarding the incorporation of (acrylonitrile butadiene styrene, ABS) polymer fibers into CG scaffolds that includes SEM images of fibers within the scaffold and failure modes under supraphysiological strain (Mozdzen et al, 2016). …”
Section: : Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…49,65 Observations of cell growth, proliferation, and adherent morphology indicated that the BMSCs on the internal surfaces of the printed scaffolds could obtain oxygen and nutrients and efficiently transport metabolic waste.…”
Section: Discussionmentioning
confidence: 99%